(untitled) (Swiss Medical Weekly, 2022)
AIM OF THE STUDY: While hospitals are adopting strategies designed to increase the overall efficiency of the healthcare system, physicians are facing expanding requirements. Such changes in work environment add new psychosocial and physical stressors. Building on a previous quantitative time-motion study, we conducted a qualitative study to better understand the work experience of internal medicine residents. METHODS: The study used a qualitative description approach, and was based on focus group discussions with residents. Data were analysed using reflexive thematic analysis. The study was conducted among all residents of the Internal Medicine division of a tertiary university hospital in Switzerland. RESULTS: Time emerged as the major determinant of residents’ daily experience, which residents want to waste on no account. Shifts are perceived as a constraining succession of distinct periods, with little room for adjustments. Moreover, residents feel held back and distracted in their progression toward the end of the shift. Under time pressure, some essential professional activities, such as caring for patients and families, dealing with medical complications and talking with consultants, may be experienced as unexpected undesirable bumps on the road. Residents describe “running through” a structured day, scattered with obstacles, and resorting to “tricks of the trade” in an attempt to influence the course of the shift. CONCLUSIONS: Time constraints are not new to medicine. However, our findings outline how time has become a constant preoccupation for internal medicine residents, permeating their daily work experience. This changing relationship with time carries the risk of undermining the foundations of clinical medicine and challenges the ability of hospitals to preserve the “sense of the profession”.